Estimation of vegetation cover percentage using visual on-screen classification in the Krueng Lagsa Watershed, Aceh Province, Indonesia - ISWAHYUDI ISWAHYUDI; RENI YUSNIAR; BOY RIZA JUANDA; MUHAMMAD RUSDI (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Iswahyudi, Yusniar R, Juanda BR, Rusdi M. 2025. Estimation of vegetation cover percentage using visual on-screen classification in the Krueng Lagsa Watershed, Aceh Province, Indonesia. Biodiversitas 26: 4297-4308. The research aims to identify land cover types contributing to the degradation of the Krueng Langsa Watershed in Aceh Province, Indonesia and analyze the Vegetation Cover Percentage (VCP). The analysis used Geographic Information System (GIS) techniques, including visual on-screen digitization of land cover classes based on RapidEye satellite imagery. The RapidEye imagery has a 5 m spatial resolution, allowing detailed classification of land cover types and accurate estimation of Vegetation Cover Percentage (VCP). The Indonesian Ministry of Forestry Regulation guided the study No. P.61/Menhut-II/2014, focusing on monitoring and evaluating watershed management. Based on image interpretation, 12 land cover classes were identified: primary dryland forest, secondary dryland forest, primary mangrove forest, secondary mangrove forest, open land, plantations, settlements, mixed dryland agriculture, rice fields, shrubs, fishponds, and water bodies. This classification highlights the dominance of vegetated land, which plays an important role in supporting biodiversity and ecosystem services in river basins. Conversely, 35.41% of the Krueng Langsa Watershed comprises non-vegetated land such as open land, settlements, fishponds, and water bodies. The fishpond land cover class occupies 14.00% of the total watershed area, potentially exerting additional environmental pressure if not managed sustainably. This information is essential for guiding watershed management strategies and biodiversity conservation planning. The VCP value of 64.59% suggests that permanent vegetation in the Krueng Langsa Watershed remains in good condition.